Determinants of Economic Performance of China - Paudel, Kamal (Humanities and Social Sciences Journal, 2021)
This paper examines the determinants of China’s economic performance during 1995-2017 as this development outcome is an economic prototype for developing countries. It employs an Ordinary Least Square technique and finds that proportion of FDI, export, government expenditure, and total debt as a percent of GDP have had a significant impact on GDP growth and GDP per capita growth of China. In addition, human capital largely contributes to economic growth. 1 percent increase in the level of human capital induces 0.21 percent increase in the economic growth for the short run and 0.39 percent increase in China in the long run. Similarly, urbanization induces a positive impact on GDP growth in the long run. Hence, a higher level of human capital and conducive business environment entice a higher inflow of FDI which helps to internalize the modern technology in different sectors of the economy for sustainable economic growth in China.